Crohn's Disease : diagnostic and prognostic indicators with special reference to granulomas - Forder, Michael David (Division of Anatomical Pathology, 2017)
The fact therefore remains that, at the present time, Crohn's disease is still an enigma. The aetiology and pathogenesis are obscure, the clinical findings and progression of the disease are unpredictable and the histological findings are often nonspecific. With this in mind, this dissertation attempts to define and document the incidence of certain histological features at presentation in a population of Crohn's disease patients from Groote Schuur Hospital. The main aim is to determine the incidence of granulomas in the study group as a whole, as well as to establish the distribution of granulomas within the bowel. A correlation between the presence of granulomas and the clinical activity of the disease (as assessed by the Crohn's Disease Activity Index) is also sought.